Censored Fractional Response Model: Estimating Heterogeneous Relative Risk Aversion of European Households - Qizhou Xiong (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
This paper estimates relative risk aversion using the observed shares of risky assets and characteristics of households from the Household Finance and Consumption Survey of the European Central Bank. Given that the risky share is a fractional response variable belonging to [0, 1], this paper proposes a censored fractional response estimation method using extremal quantiles to approximate the censoring thresholds. Considering that participation in risky asset markets is costly, I estimate both the heterogeneous relative risk aversion and participation cost using a working sample that includes both risky asset holders and non-risky asset holders by treating the zero risky share as the result of heterogeneous self-censoring. Estimation results show lower participation costs and higher relative risk aversion than what was previously estimated. The estimated median relative risk aversions of eight European countries range from 4.6 to 13.6. However, the results are sensitive to households' perception of the risky asset market return and volatility.
urn:nbn:de:gbv:3:2-48604
Keywords: C21; C24; E44; G11; 330; European household finance; relative risk aversion; censored fractional response model; extremal quantile regression